Pleural controversies: image guided biopsy vs. thoracoscopy for undiagnosed pleural effusions? - Dixon, Giles; de Fonseka, Duneesha; Maskell, Nick (Journal of Thoracic Disease, 2015)
Undiagnosed pleural effusions present an increasing diagnostic burden upon healthcare providers internationally. The investigation of pleural effusions often requires the acquisition of tissue for histological analysis and diagnosis. Historically there were two options for tissue biopsy: a ‘gold standard’ surgical biopsy or a “blind” closed pleural biopsy. Over the last decade however, image-guided Tru-cut biopsies and local anaesthetic thoracoscopic (local anaesthetic thoracoscopy) biopsies have become more widespread. Imageguided techniques acquire samples under ultrasound (US) or computed tomography (CT) guidance whereas LAT involves the direct visualisation and biopsy of the pleura with pleuroscopy. Both techniques have been shown to be superior to ‘blind’ closed pleural biopsy for the diagnosis of pleural or metastatic malignancy. However, closed biopsy remains a viable method of investigation in areas of high incidence of tuberculosis (TB). Beyond this, each investigative technique has its own advantages and disadvantages. Image-guided biopsy is less invasive, usually carried out as an outpatient procedure, and enables tissue biopsy in frail patients and those with pleural thickening but no pleural fluid. Local anaesthetic thoracoscopy (LAT) provides diagnostic and therapeutic capabilities in one procedure. Large volume thoracentesis, multiple pleural biopsies and talc poudrage can be carried out in a single procedure. The overall diagnostic yield is similar for both techniques, although there are no large-scale direct comparisons. Both techniques share low complication rates.